Nano-carbon-based slow-release saline-alkali soil conditioner and gradient controlled release method thereof
Through the gradient controlled release design of nano-carbon-based slow-release saline-alkali land conditioner, the problems of low desalination efficiency, soil structure deterioration and imbalance of nutrient supply in saline-alkali land restoration have been solved, efficient restoration and long-term stability of saline-alkali land have been achieved, and the economy and sustainability of saline-alkali land management have been improved.
Patent Information
- Application Number
- CN202510836671.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-21
- Publication Date
- 2025-09-26
AI Technical Summary
The existing saline-alkali land remediation materials lack functional synergy, resulting in low desalination efficiency, soil structure deterioration, and unbalanced nutrient supply. In addition, the materials have a short service life and slow environmental response, making it difficult to achieve long-term stability in complex saline-alkali systems.
A nano-carbon-based slow-release saline-alkali land conditioner is used. Through the gradient controlled release design of layered nano-carbon matrix and humic acid intercalation complex, pH-responsive cross-linking agent, calcium ion and phosphate modifier, a multifunctional conditioner is constructed to achieve sodium ion adsorption, slow release of nutrients and soil structure improvement.
It achieves rapid desalination of saline-alkali land, continuous nutrient supply, soil structure improvement, reduces salt toxicity, improves the accuracy of restoration and the long-term stability of materials, simplifies the construction process, and reduces management costs.
Smart Images

Figure CN120699632A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of soil remediation and saline-alkali land management, and in particular to a nano-carbon-based slow-release saline-alkali land conditioner and a gradient controlled-release method thereof. Background Art
[0002] With the continued expansion of saline-alkali soils worldwide, the development of efficient and low-cost saline-alkali land remediation materials has become a research hotspot in the agricultural and environmental fields. Traditional remediation technologies rely primarily on physical desalination, chemical conditioning, and biological improvement, with ion adsorption materials and slow-release fertilizers being the most widely used. However, saline-alkali land remediation involves multiple objectives, including desalination, acidification, structural improvement, and nutrient supply. Existing materials often focus on a single function and are unable to coordinately address complex saline-alkali obstacles, resulting in fragmented and poorly sustainable remediation effects, which severely restricts large-scale remediation efforts.
[0003] At present, saline-alkali land remediation materials generally face the core defect of insufficient functional synergy. Although ion adsorption materials can quickly reduce the concentration of sodium ions in the soil, the single desalination process can easily destroy the colloidal structure, causing soil compaction or nutrient loss, which in turn aggravates crop growth stress. Although slow-release fertilizers can extend the nutrient supply cycle, they lack the intelligence to dynamically respond to saline-alkali environments. Under pH fluctuations and high salt stress, functional groups are prone to inactivation or premature degradation, resulting in waste of resources and secondary pollution. In addition, traditional materials have poor physical and chemical stability. They are prone to agglomeration or structural collapse under long-term water-salt alternation, mechanical external forces and microbial effects, resulting in a sharp drop in remediation performance, forcing repeated applications to increase costs. The above problems expose the limitations of the applicability of single-functional materials in complex saline-alkali systems, and there is an urgent need to achieve breakthroughs in multifunctional integration and long-term stability through material design innovation.
[0004] In response to the systemic problems in existing technologies such as the separation of desalination, acidification, and structural improvement, as well as the short service life of materials and slow environmental response, the present invention proposes a nano-carbon-based slow-release saline-alkali land conditioner and a gradient controlled release method thereof. Summary of the Invention
[0005] In response to the shortcomings of the existing technology, the present invention provides a nano-carbon-based slow-release saline-alkali land conditioner and a gradient controlled release method thereof, which solves the multiple synergistic problems of low desalination efficiency, soil structure deterioration, unbalanced nutrient supply and poor material functional sustainability in saline-alkali land remediation.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: The first aspect of the present invention provides a nano-carbon-based slow-release saline-alkali land conditioner, which is composed of the following components in percentage by mass: Layered nanocarbon matrix: 45-65%, specific surface area 750-950m 2 / g, pore size is 2-50nm; Humic acid intercalation complex: 15-22%, carboxyl density 3.0-3.4mmol / g; pH-responsive crosslinker: 5-12%, dimethylaminoethyl methacrylate-acrylic acid copolymer, molecular weight 40-80 kDa; Calcium ion modifier: 5-15%, loaded in the form of CaCl2, with a loading concentration of 0.5-0.7 mol / L; Phosphate modifier: 5-10%, loaded in the form of NaH2PO4, with a loading concentration of 0.3-0.5 mol / L.
[0007] Preferably, the preparation method of the layered nanocarbon matrix includes: The biomass raw material is heated to 550-650°C at 8-12°C / min under nitrogen protection and cracked for 1.5-2.5 hours, then mixed with KOH at a mass ratio of 1:2-1:4, and calcined at 800-900°C for 0.8-1.2 hours.
[0008] The nanocarbon matrix is prepared by oxygen-limited cracking and KOH activation of biomass (rice husk / straw), forming a high specific surface area and hierarchical pore structure. The mesoporous structure can + 、Cl - Plasma creates a confined adsorption effect, while micropores (<2nm) enhance water retention through capillary action. During KOH activation, the biomass carbon skeleton undergoes a redox reaction with K⁺, forming abundant surface defect sites that provide anchoring points for humic acid intercalation.
[0009] Preferably, the preparation method of the humic acid intercalation composite comprises: Humic acid and nano-carbon matrix are mixed in a mass ratio of 1:4.5-1:5.5, and ultrasonically treated at 35-45 kHz for 1.5-2.5 hours in a buffer solution with a pH of 8.5-9.5.
[0010] Humic acid molecules are intercalated into the nanocarbon interlayers through ultrasonic dispersion. Their carboxyl groups (3.0-3.4 mmol / g) and phenolic hydroxyl functional groups form hydrogen bonds and π-π conjugation with surface defects in the nanocarbon, forming a stable layered composite structure. This intercalation design not only increases the cation exchange capacity (CEC) of the material but also inhibits nanocarbon particle aggregation through the steric hindrance of the humic acid molecular chains, maintaining a high specific surface area activity.
[0011] Preferably, the loading method of the calcium ion modifier and the phosphate modifier includes: Alternately immerse in 0.5-0.7 mol / LCaCl2 solution and 0.3-0.5 mol / LNaH2PO4 solution, the cycle number is 3-5 times, and the immersion time each time is 1.0-1.5 hours.
[0012] Calcium ions (Ca 2+ ) and phosphate (PO4 3- ) are loaded on the surface and pores of the material by alternating impregnation. 2+ It binds to the carboxyl site of humic acid by electrostatic adsorption, PO4 3- It is fixed in the mesoporous channel by chemical precipitation (CaHPO4). 2+ -Internal PO4 3- "The ion storage structure of Na + The adsorption process triggers Ca 2+ Directed release of PO4 3- Slow dissolution through pore diffusion achieves synergy between salt replacement and phosphorus supplementation.
[0013] Preferably, the coating method of the pH-responsive cross-linking agent includes: Fluidized bed spray technology is used, the spray rate is 3-5mL / min, the inlet air temperature is 50-60℃, and the coating amount is 8-12% of the total mass of the particles.
[0014] Dimethylaminoethyl methacrylate-acrylic acid copolymer serves as a crosslinker. Its molecular chain contains both pH-sensitive groups (tertiary amines) and hydrophilic groups (carboxyls). In alkaline environments (pH > 8.3), deprotonation of the tertiary amines triggers the copolymer to swell, exposing nanocarbon adsorption sites. When the pH decreases, the crosslinker shrinks to form a dense coating, slowing nutrient release. The molecular weight range (40-80 kDa) ensures controlled degradation by soil microorganisms.
[0015] The second invention of the present invention provides a gradient controlled release method of a nano-carbon-based slow-release saline-alkali land conditioner, which comprises the following steps: S1. pH-responsive salt adsorption: When the soil pH is greater than 8.3, the negative charge on the surface of the nanocarbon is enhanced, and the Na + , and its adsorption process conforms to the pseudo-second-order kinetic model; S2, microbial-driven nutrient release: soil microorganisms decompose crosslinkers to release available nitrogen and phosphorus, where the microbial activity threshold is a soil respiration rate ≥ 15 μgCO2 / g·h; S3, ion exchange dynamic equilibrium: each adsorption of 1 mol Na + Synchronously release 0.28-0.32 molCa2+ .
[0016] When the soil pH is greater than 8.3, the surface zeta potential of nanocarbon drops below -35 mV, the electrostatic repulsion weakens, and Na + The carboxyl groups provided by humic acid intercalation strengthen the Na + The adsorption process followed a pseudo-second-order kinetic model, indicating that chemical adsorption was the dominant mechanism. The adsorption equilibrium time (2.5-3.5 h) was set based on the optimal match between the soil solution ion diffusion rate and the material adsorption site density.
[0017] The degradation rate of the crosslinker is regulated by the activity of soil microorganisms. When the microbial respiration rate is ≥15μgCO2 / g·h, the esterase and oxidase secreted by the microorganisms can break the ester and amide bonds in the copolymer molecular chain, releasing the encapsulated fast-acting nitrogen (NH4 + 、NO3 - ) and available phosphorus (HPO4 2- The release kinetics were described by the first-order equation (available nitrogen) and the Higuchi model (available phosphorus), reflecting the synergistic effect of diffusion and matrix dissolution.
[0018] Each adsorption of 1 mol Na + Synchronously release 0.28-0.32 molCa 2+ , the ratio is composed of humic acid-Ca 2+ Binding strength and Na + The equilibrium constant of the ion exchange reaction (logK = 2.8-3.1) indicates that the reaction tends to form Ca 2+ , thereby continuously reducing the soil sodium adsorption ratio (SAR). The released Ca 2+ Further with the Na in soil colloids + Replacement occurs, promoting the formation of aggregate structure, and PO4 3- The slow release of free Al is fixed by precipitation reaction. 3+ 、Fe 3+ Isotropic salt ions.
[0019] Preferably, in step S1: Na + The adsorption capacity is 4.2-5.0mmol / g; The equilibrium time in the pseudo-second-order kinetic model is 2.5-3.5h.
[0020] Preferably, in step S2, the release rate of available nitrogen is 0.5-0.8 mg / kg·d, and the release rate of available phosphorus is 0.3-0.6 mg / kg·d.
[0021] Preferably, in step S3: The equilibrium constant log K of the ion exchange reaction is 2.8-3.1; Ca in soil solution after replacement 2+ The concentration is maintained at 0.8-1.2mmol / L.
[0022] The third invention of the present invention provides an application of the above-mentioned method in saline-alkali land restoration, and the application method is as follows: When the soil pH is greater than 8.3, apply 0.3-0.7 tons / mu of conditioner; When the available phosphorus content is less than 15 mg / kg, apply phosphate solution The present invention provides a nano-carbon-based slow-release saline-alkali soil conditioner and a gradient controlled-release method thereof. It has the following beneficial effects: 1. The present invention is based on a nanocarbon-humic acid layered composite structure, which preferentially adsorbs sodium ions through a hydrogen bond network to achieve rapid desalination. At the same time, the nutrients in the mesoporous channels are slowly released in stages according to crop needs. This design breaks the single function of traditional materials, while reducing soil salt damage, providing continuous nutrition supply for seed germination and root growth, avoiding secondary stress on crop growth caused by the desalination process.
[0023] 2. The "Ca" constructed by the gradient ion modification process of the present invention 2+ -PO4 3- "The graded release system allows surface calcium ions to quickly replace sodium ions, reducing saline-alkali toxicity. Internal phosphate groups and calcium ions form cements to reshape the soil aggregate structure. This synergistic mechanism not only avoids soil compaction caused by single desalination, but also creates an air-permeable and water-retaining microenvironment, significantly improving soil cultivability.
[0024] 3. The present invention adopts pH-responsive cross-linker coating technology to dynamically match the nutrient release rate with the microbial metabolic intensity. When the root secretions stimulate the microbial activity to reach the threshold, the cross-linker selectively degrades to trigger nutrient release, achieving "supply on demand", effectively preventing nutrient loss and secondary salt enrichment, and improving the accuracy of repair.
[0025] 4. The three-dimensional interpenetrating network of the nanocarbon skeleton and humic acid of the present invention inhibits functional group oxidation and particle agglomeration through the dual effects of chemical bonding and spatial confinement. The hierarchical pore structure provides a physical protection barrier for the active components, ensuring that the material maintains structural integrity and functional stability under complex environments such as long-term water-salt alternation and mechanical external forces.
[0026] 5. The present invention integrates functions such as desalination, acidification, structural improvement, and nutrient release into a single material. The high specific surface area and gradient release design of the nanocarbon matrix reduce the application amount per unit area. This integrated solution simplifies the construction process, reduces subsequent maintenance requirements, and provides an economical and efficient solution for large-scale saline-alkali land management. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Flowchart of the gradient controlled release method of the present invention. DETAILED DESCRIPTION
[0028] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the present specification. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0029] Please see the attached Figure 1 The present invention provides a nano-carbon-based slow-release saline-alkali land conditioner and a gradient controlled release method thereof through multiple embodiments. Specific embodiments 1-3 are as follows: Example 1: Raw material ratio (wt%): Layered nanocarbon matrix: 55% (specific surface area 850m 2 / g, pore size 5-45nm); Humic acid intercalation complex: 18.5% (carboxyl density 3.2 mmol / g); pH-responsive cross-linker: 10% (molecular weight 60 kDa); Calcium ion modifier (CaCl2): 10.5% (loading concentration 0.6 mol / L); Phosphate modifier (NaH2PO4): 6% (loading concentration 0.4 mol / L).
[0030] Preparation steps: Preparation of nanocarbon matrix: Rice husk was crushed to 100 mesh and dried at 105 °C for 12 h; Under nitrogen protection, the temperature was raised to 600°C at 10°C / min and kept at this temperature for 2 h; Mixed with KOH in a mass ratio of 1:3 and calcined at 850 °C for 1 h; The product was washed with deionized water until pH = 7.0 and dried in vacuum at 60 °C for 24 h.
[0031] Humic acid intercalation compound: Humic acid was dissolved in Tris-HCl buffer (pH = 9.0) (concentration 75 g / L); Mix nanocarbon and humic acid in a ratio of 5:1 (dry basis) and treat with ultrasound at 40 kHz for 2 h. Centrifuge at 6000 rpm for 15 min and dry at 60°C to a moisture content of 4.8%.
[0032] Ion gradient modification: Immerse in 0.6 mol / LCaCl2 solution (solid-liquid ratio 1:12) and shake at 25°C for 21 h; Alternately immerse in 0.4 mol / L NaH2PO4 solution 4 times, 1.25 h each time; After drying at 60℃, Ca 2+ Loading capacity 1.0mmol / g, PO4 3- Loading capacity 0.5mmol / g.
[0033] Crosslinker coating: Fluidized bed spray coating, inlet air temperature 55 °C, spray rate 4 mL / min; After coating, the moisture content of the particles is 4.5%, and the cross-linking agent accounts for 10%.
[0034] Example 2: Raw material ratio (wt%): Layered nanocarbon matrix: 65% (specific surface area 750m 2 / g, pore size 2-40nm); Humic acid intercalation complex: 15% (carboxyl density 3.0 mmol / g); pH-responsive cross-linker: 5% (molecular weight 80 kDa); Calcium ion modifier (CaCl2): 10% (loading concentration 0.7 mol / L); Phosphate modifier (NaH2PO4): 5% (loading concentration 0.5 mol / L).
[0035] Preparation steps: Preparation of nanocarbon matrix: Corn straw was crushed to 80 mesh and dried at 105°C for 24 h; Under nitrogen protection, the temperature was raised to 550°C at 12°C / min and kept at this temperature for 1.5 h; Mixed with KOH in a mass ratio of 1:4 and calcined at 800 °C for 1.2 h; Wash with deionized water until pH = 6.5 and dry at 60℃ for 24h.
[0036] Humic acid intercalation compound: Humic acid was dissolved in pH=8.5 buffer (concentration 100g / L); Nanocarbon: humic acid = 5.5:1 mixture, 35kHz ultrasonic treatment for 2.5h; Centrifuge at 6000 rpm for 15 min and dry at 60°C to a moisture content of 5.0%.
[0037] Ion gradient modification: Immerse in 0.7 mol / LCaCl2 solution (solid-liquid ratio 1:10) and shake at 25°C for 24 h; Alternately immerse in 0.5 mol / L NaH2PO4 solution 5 times, 1.0 h each time; After drying at 60℃, Ca 2+ Loading capacity 1.2mmol / g, PO4 3- Loading capacity 0.6mmol / g.
[0038] Crosslinker coating: Fluidized bed spray coating, inlet air temperature 50 °C, spray rate 5 mL / min; After coating, the moisture content of the particles is 5.0%, and the cross-linking agent accounts for 8%.
[0039] Example 3: Raw material ratio (wt%): Layered nanocarbon matrix: 45% (specific surface area 950m 2 / g, pore size 10-50nm); Humic acid intercalation complex: 22% (carboxyl density 3.4mmol / g); pH-responsive cross-linker: 12% (molecular weight 40 kDa); Calcium ion modifier (CaCl2): 15% (loading concentration 0.5 mol / L); Phosphate modifier (NaH2PO4): 6% (loading concentration 0.3 mol / L).
[0040] Preparation steps: Preparation of nanocarbon matrix: Rice husk / corn straw (1:1) was crushed to 120 mesh and dried at 105 °C for 8 h; Under nitrogen protection, the temperature was raised to 650°C at 8°C / min and kept at this temperature for 2.5 h; Mixed with KOH in a mass ratio of 1:2 and calcined at 900 °C for 0.8 h; Wash with deionized water until pH = 7.5 and dry at 60℃ for 24h.
[0041] Humic acid intercalation compound: Humic acid was dissolved in pH = 9.5 buffer (concentration 50 g / L); Nanocarbon: humic acid = 4.5:1 mixture, 45kHz ultrasonic treatment for 1.5h; Centrifuge at 6000 rpm for 15 min and dry at 60°C to a moisture content of 4.5%.
[0042] Ion gradient modification: Immerse in 0.5 mol / LCaCl2 solution (solid-liquid ratio 1:15) and shake at 25°C for 18 h; Alternately immerse in 0.3 mol / L NaH2PO4 solution 3 times, 1.5 h each time; After drying at 60℃, Ca 2+ Loading capacity 0.8mmol / g, PO4 3- Loading capacity 0.4mmol / g.
[0043] Crosslinker coating: Fluidized bed spray coating, inlet air temperature 60 ° C, spray rate 3 mL / min; After coating, the moisture content of the particles is 4.0%, and the cross-linking agent accounts for 12%.
[0044] Comparative Examples 1-8: Comparative Example 1: Compared with Example 1, the difference is that the humic acid intercalation step is omitted, the humic acid and the nano-carbon matrix are directly mechanically mixed (dry mixing for 5 minutes), and no ultrasonic treatment is performed. The other steps and parameters are the same.
[0045] Comparative Example 2: Compared with Example 1, the difference is that the molecular weight of the pH-responsive cross-linking agent exceeds the scope of the claims, and a dimethylaminoethyl methacrylate-acrylic acid copolymer with a molecular weight of 25 kDa is used. The other steps and parameters are the same.
[0046] Comparative Example 3: Compared with Example 1, the difference is that the calcium ion and phosphate modification adopts a single immersion method, only immersing in 0.6 mol / LCaCl2 solution once (immersion time 21 h), without alternating immersion in NaH2PO4 solution, and the other steps and parameters are the same.
[0047] Comparative Example 4: Compared with Example 1, the difference is that the mass ratio of KOH to biomass in the preparation of the nanocarbon matrix exceeds the scope of the claim, and KOH:biomass=1:1 is used, the calcination temperature is maintained at 850°C, and the other steps and parameters are the same.
[0048] Comparative Example 5: Compared with Example 1, the difference is that the pH-responsive cross-linking agent coating step is omitted, and uncoated humic acid-nanocarbon composite particles are directly used. The other steps and parameters are the same.
[0049] Comparative Example 6: Compared with Example 1, the difference is that the calcium ion loading concentration exceeds the scope of the claims, and 1.0 mol / LCaCl2 solution is used for impregnation, and the other steps and parameters are the same.
[0050] Comparative Example 7: Compared with Example 1, the difference is that the amount of humic acid intercalation compound exceeds the upper limit of the claim, the proportion of humic acid is increased to 25%, the proportion of nanocarbon matrix is correspondingly adjusted to 50%, and the remaining steps and parameters are the same.
[0051] Comparative Example 8: Compared with Example 1, the difference is that the pyrolysis temperature of the nanocarbon matrix exceeds the range of the claims, and the temperature is increased to 700° C. at 15° C. / min under nitrogen protection for pyrolysis. The other steps and parameters are the same.
[0052] Test Example 1-5: Test Example 1: Salt Adsorption Performance Comparative Test Experiment Description Purpose of the experiment: The performance differences of the nano-carbon-based sustained-release conditioning agent (Example 1) and its comparative examples (Comparative Examples 1, 3, 4, and 8) in terms of salt adsorption capacity, kinetics, and stability were verified.
[0053] Experimental steps: Preparation of simulated saline-alkali soil solution: Prepare NaCl solution (conductivity EC = 15dS / m, corresponding to Na + concentration of approximately 120 mmol / L); CaCl2 (1.2mmol / L) and MgSO4 (0.8mmol / L) were added to simulate the ionic composition of saline-alkali soil.
[0054] Adsorption experimental conditions setting: Take 50mL of simulated saline-alkali soil solution in a conical flask; Add 0.5 g of the conditioning agent sample (Example 1, Comparative Examples 1 / 3 / 4 / 8) and shake at a constant temperature of 25°C (150 rpm); Parallel experimental groups (n=3) were set up.
[0055] Dynamic sampling and concentration determination: 2 mL samples were collected at 0.5 h, 1 h, 2 h, 3 h, 5 h, 8 h, 12 h, and 24 h; After sampling, filter through a 0.45 μm filter membrane immediately; The Na content in the filtrate was determined by atomic absorption spectrometry. + Concentration, calculate adsorption amount .
[0056] Adsorption equilibrium determination: When sampling 3 times in a row When the fluctuation is less than 2%, it is judged that the adsorption equilibrium has been reached; Record the equilibrium time and maximum adsorption capacity .
[0057] Persistence test: The adsorbed saturated conditioner was washed with deionized water three times and dried at 60°C; The adsorption-desorption cycle was repeated 5 times, and the ratio of the fifth adsorption capacity to the first adsorption capacity (retention rate) was calculated.
[0058] Experimental data: Table 1: Experiment 1 salt adsorption performance comparison test data table Data analysis description: Example 1: Due to the layered nanocarbon-humic acid composite structure and gradient ion modification, the adsorption capacity (4.72 mmol / g) is significantly higher than that of the comparative example; Comparative Example 1 (no ultrasonic intercalation): Humic acid was not effectively embedded in the nanocarbon layers, and the adsorption capacity decreased by 32.8%; Comparative Example 3 (Single Impregnation): Lack of PO4 3- With sustained-release compensation, the persistence was reduced to 78.1%; Comparative Example 4 (Insufficient KOH Activation): The specific surface area decreased, resulting in an adsorption capacity of only 2.97 mmol / g; Comparative Example 8 (pyrolysis temperature was too high): the carbon skeleton structure collapsed and the equilibrium time was extended to 3.8 h.
[0059] Experimental summary: This experiment reveals the synergistic mechanism of the layered composite structure design and gradient ion modification of the nanocarbon-based sustained-release conditioner by comparing the differences in salt adsorption performance of different preparation processes. In Example 1, humic acid molecules are embedded into the interlayer gaps of the nanocarbon matrix through ultrasound-assisted intercalation, and its carboxyl groups form a stable hydrogen bond network with the oxygen-containing functional groups on the surface of the nanocarbon, which significantly improves the ion exchange capacity of the material. This structural characteristic makes Na + It can be captured through both physical adsorption (mesopore confinement effect) and chemical adsorption (carboxyl coordination), resulting in a high adsorption capacity of 4.72 mmol / g in a simulated saline-alkali soil environment. In contrast, in Comparative Example 1, due to the omission of the ultrasonic intercalation step, humic acid adheres to the nanocarbon surface solely through physical mixing, resulting in insufficient adsorption site density and a reduced adsorption capacity of 3.15 mmol / g, confirming the decisive role of the layered composite structure in adsorption performance.
[0060] The KOH gradient activation process directly affects the adsorption kinetics of the nanocarbon matrix by regulating its pore structure. In Example 1, the biomass raw material was subjected to oxygen-limited cracking at 550-650 ° C, and then etched by KOH at high temperature (850 ° C) to form hierarchical pores (2-50 nm) dominated by mesopores. + Diffusion provides a fast transmission path, and the equilibrium time is shortened to 2.9h. However, in Comparative Example 4, the amount of KOH used is insufficient (mass ratio 1:1), and the specific surface area of the nanocarbon is limited (<750m2 / g), the proportion of mesopores decreased, resulting in Na + Diffusion within the micropores was hindered, the equilibrium time was extended to 5.2 hours, and the adsorption capacity decreased simultaneously. This shows that precise control of the KOH activation ratio and temperature is the key to constructing efficient adsorption channels.
[0061] The calcium / phosphate gradient modified layer constructed by the alternating impregnation method ensures the adsorption persistence through the dynamic equilibrium mechanism of ion replacement. 2+ With internal PO4 3- The gradient distribution of Na + The adsorption process is accompanied by Ca 2+ The directional release of the replacement reaction equilibrium constant logK is stable in the range of 2.8-3.1, so that 89.3% of the capacity is still maintained after 5 adsorption-desorption cycles. 3- The slow release compensation leads to Ca 2+ The release rate was too fast, the ion exchange equilibrium was destroyed, and the retention rate dropped to 78.1%. This further verified the necessity of gradient ion modification to maintain long-term adsorption performance.
[0062] Test Example 2: Nutrient Controlled Release Performance Comparative Test Experiment Description Purpose of the experiment: The performance differences of the nano-carbon-based sustained-release conditioner (Example 1) and its comparative examples (Comparative Examples 2, 5, and 7) in terms of the quick-acting nitrogen / phosphorus release rate, sustained-release period, and microbial response threshold were verified.
[0063] Experimental steps: Simulated soil environment construction: The surface soil (0-20 cm) from non-saline-alkali land was collected, passed through a 2 mm sieve, and sterilized at 121 °C for 30 min; Mix soil and water at a ratio of 1:5 (w / v), and add glucose (0.1 g / kg) to activate indigenous microorganisms.
[0064] Conditioning agent buried and condition control: 5 g of the conditioner sample (Example 1, Comparative Examples 2 / 5 / 7) was evenly buried in 200 g of sterilized soil; The soil moisture was controlled to 60% of the field capacity and the culture temperature was kept constant at 25°C; A low-activity group (natural microorganisms) and a high-activity group (inoculated with Bacillus subtilis, respiration rate ≥ 20 μgCO2 / g·h) were set up.
[0065] Dynamic sampling and nutrient determination: 5 g of soil samples were collected at 1 d, 3 d, 7 d, 14 d, 21 d, and 28 d; Extract with 2 mol / L KCl (soil:liquid = 1:10), shake for 1 h, and then centrifuge and filter; Available nitrogen (NH4 + +NO3 - ) was determined by indigo blue colorimetry; Available phosphorus (HPO4 2- ) was determined by the molybdenum antimony colorimetric method.
[0066] Microbial response threshold determination: The soil respiration rate was adjusted by gradient (5-25 μgCO2 / g·h), and the activity was controlled by adjusting the amount of glucose added; The mutation points of the available nitrogen release rate at each activity threshold were determined (slope change > 50%).
[0067] Experimental data: Table 2: Experiment 2 Nutrient Controlled Release Performance Comparison Test Data Data analysis description: Example 1: The pH-responsive cross-linker (molecular weight 60 kDa) coating was controllably degraded under the action of microorganisms, with a stable release rate of available nitrogen at 0.63 mg / kg·d and a sustained release period of available phosphorus of 18.7 days. The microbial activity threshold (14.9 μgCO2 / g·h) was consistent with the claimed value (≥15 μgCO2 / g·h). Comparative Example 2 (cross-linker molecular weight 25 kDa): The low molecular weight cross-linker degraded prematurely, the fast-acting nitrogen release rate soared to 1.25 mg / kg·d, and the sustained-release period was shortened to 9.3 days; Comparative Example 5 (no cross-linking agent coating): Direct nutrient exposure resulted in an excessively rapid initial release of available nitrogen (0.91 mg / kg·d), and the microbial response threshold increased to 23.6 μgCO2 / g·h, resulting in a loss of controlled release. Comparative Example 7 (excessive humic acid): The high proportion of humic acid (25%) prevented microorganisms from contacting the cross-linking agent, inhibited the release rate of fast-acting nitrogen to 0.42 mg / kg·d, and abnormally prolonged the sustained release period of available phosphorus.
[0068] Experimental Summary: This experiment, by comparing the differences in nutrient controlled-release performance obtained from different preparation processes, revealed the synergistic effect of pH-responsive crosslinker coating and microbial-driven release mechanisms in the nanocarbon-based sustained-release conditioner. In Example 1, dimethylaminoethyl methacrylate-acrylic acid copolymer (molecular weight 60 kDa) was sprayed through a fluidized bed to form a uniform coating. The tertiary amine groups in the molecular chain were selectively cleaved by esterases secreted by microorganisms, resulting in a stable release of available nitrogen (0.63 mg / kg·d). In contrast, in Comparative Example 2, due to the use of a crosslinker with a molecular weight of 25 kDa, the excessively short molecular chain resulted in insufficient coating density, accelerated microbial degradation, and a rapid release rate of available nitrogen, reaching 1.25 mg / kg·d. This demonstrates the critical role of the crosslinker molecular weight range in regulating the controlled-release rate.
[0069] The proportion of humic acid intercalation complexes directly affects the temporal and spatial matching of nutrient release. In Example 1, when the humic acid accounted for 18.5%, the π-π conjugation between its carboxyl groups and the nanocarbon surface formed a stable three-dimensional network, which not only provided active sites for microbial attachment, but also delayed the degradation of the cross-linker through steric hindrance. This design allows the effective phosphorus sustained-release period to reach 18.7 days, which coincides with the peak period of crop phosphorus demand. In Comparative Example 7, because the humic acid proportion was increased to 25%, the excess carboxyl groups formed hydrogen bonds with the cross-linker molecular chains, hindering microorganisms from contacting the degradation sites, resulting in an abnormal extension of the effective phosphorus release period to 26.8 days, and the quick-acting nitrogen release rate was suppressed to 0.42 mg / kg·d, indicating that the humic acid ratio must be strictly limited to balance the adsorption and release functions.
[0070] The precise control of the microbial response threshold further demonstrates the intelligence of material design. In Example 1, the synergistic effect of the cross-linker coating thickness (10%) and molecular weight (60kDa) ensures that nutrient release is triggered only when the soil respiration rate is ≥14.9μgCO2 / g·h, which is consistent with the law that crop root secretions stimulate microbial activity. In Comparative Example 5, due to the omission of the cross-linker coating, the nutrients are directly exposed, resulting in a decoupling of release from microbial activity. The threshold is raised to 23.6μgCO2 / g·h, and on-demand release cannot be achieved. This proves that the dynamic matching of the pH-responsive coating and microbial activity is the core innovation to break through the bottleneck of blind release of traditional materials.
[0071] Test Example 3: Ion Exchange Synergy Comparative Test Experimental Description Purpose of the experiment: Verify the nano-carbon based sustained-release conditioning agent (Example 1) and its comparative examples (Comparative Examples 3 and 6) in Ca 2+ / Na + Replacement efficiency, PO4 3- Performance differences in sustained-release capacity and ion balance regulation.
[0072] Experimental steps: Construction of dynamic replacement system for simulated saline-alkali land: Prepare high sodium ion solution: NaCl (120 mmol / L), CaCl2 (1.2 mmol / L), MgSO4 (0.8 mmol / L), initial pH = 8.5; 0.1 mol / L Tris buffer was added to maintain pH stability.
[0073] Ion exchange experimental conditions setting: 100 mL of the above solution was placed in a reactor, and 1.0 g of the conditioning agent sample (Example 1, Comparative Example 3 / 6) was added; Constant temperature magnetic stirring (25°C, 200 rpm), continuous nitrogen flow to avoid CO2 interference; Parallel experimental groups (n=3) were set up.
[0074] Dynamic ion concentration monitoring: 3 mL samples were collected at 0.5 h, 1 h, 2 h, 4 h, 8 h, 12 h, and 24 h; Immediately filter through a 0.22 μm filter membrane and divide the filtrate into 3 centrifuge tubes: Na + : Atomic absorption spectrometer (wavelength 589nm); Ca 2+ : EDTA complexometric titration; PO4 3- : Ammonium molybdate-ascorbic acid colorimetry (wavelength 880 nm).
[0075] Calculation of substitution equilibrium constant: According to the Na + , Ca 2+ concentration, calculate the equilibrium constant: ; PO4 3- Cumulative release determination: Collect all the sample filtrates and determine the total PO4 3- Release amount, converted to mg / kg dry soil.
[0076] Experimental data: Table 3: Experiment 3 ion exchange synergy comparison test data Data analysis description: Example 1: Gradient ion modification layer constructed by alternating impregnation method (surface Ca 2+ -Internal PO4 3- ) Realize Ca 2+ / Na +Replacement molar ratio 0.30, PO4 3- The cumulative release amount is 28.5 mg / kg, logK=2.95, which meets the requirements of dynamic equilibrium design; Comparative Example 3 (Single Impregnation): Only Ca was loaded 2+ The replacement molar ratio was reduced to 0.18, PO4 3- The release was insufficient (13.2 mg / kg), and the log K deviated to 2.34, indicating that the lack of phosphate compensation would disrupt the ion balance; Comparative Example 6 (Ca 2+ Excessive CaCl2 (1.0 mol / L) leads to Ca 2+ Competing for adsorption sites, the replacement molar ratio increased abnormally to 0.42, but PO4 3- Due to the early consumption of precipitation reaction, logK dropped to 1.82, proving that the calcium / phosphorus loading ratio needs to be strictly limited.
[0077] Experimental summary: This experiment reveals the regulation mechanism of the calcium / phosphate gradient modified layer on the dynamic balance of ions in the nano-carbon-based sustained-release conditioner by comparing the ion replacement performance differences of different preparation processes. 2+ -Internal PO4 3- The gradient structure achieves synergistic ion exchange through a phased release mechanism. 2+ Rapid replacement of Na by electrostatic adsorption + (replacement molar ratio 0.30), while the internal PO4 3- With excess Ca in solution 2+ Combined to form CaHPO4 precipitate, avoiding Ca 2+ This design makes PO4 3- The cumulative release amount reached 28.5 mg / kg, and the equilibrium constant logK of the replacement reaction was stable at 2.95, which was highly consistent with the thermodynamic law of ion exchange in soil solution. 3- compensatory release of Ca 2+ Premature exhaustion caused the replacement molar ratio to drop sharply to 0.18, verifying the necessity of gradient ion modification.
[0078] Precise control of calcium ion loading concentration is the key to maintaining replacement balance. In Example 1, the alternating loading of 0.6 mol / L CaCl2 impregnation concentration and 0.4 mol / L NaH2PO4 ensures that Ca 2+ With PO4 3- The molar ratio is close to 1.5:1, which not only meets the rapid replacement requirements but also avoids the precipitation reaction from happening too early.2 + Occupying the nanocarbon pores leads to PO4 3- Adsorption sites are blocked, PO4 3- While the release amount abnormally increased to 34.7 mg / kg, the logK value decreased to 1.82 due to the imbalance of ionic strength, proving that strict limitation of the calcium / phosphorus loading ratio is crucial to maintaining ion exchange efficiency.
[0079] The stability of the ion exchange equilibrium constant further reflects the scientific nature of the material design. In Example 1, the gradient modified layer delays the Ca 2+ The release rate of Ca 2+ / Na + The replacement reaction is always in a quasi-equilibrium state, and the fluctuation range of logK value is controlled within ±0.12. This feature enables the conditioner to continuously desalinate in the high sodium environment of saline-alkali land without being affected by Ca 2+ Instantaneous overdose causes soil compaction. However, due to the lack of buffering effect of gradient structure, the logK value of comparative example 3 fluctuates by ±0.15, and PO4 3- The release amount is only 13.2 mg / kg, which cannot meet the long-term demand of crops for phosphorus, highlighting the irreplaceable role of the alternating impregnation process in the dynamic balance of ions.
[0080] Test Example 4: Material Stability Comparative Test Experiment Description Purpose of the experiment: The performance differences of the nano-carbon-based sustained-release conditioning agent (Example 1) and its comparative examples (Comparative Examples 1 and 7) in terms of anti-agglomeration, functional group stability and mechanical strength were verified.
[0081] Experimental steps: Anti-agglomeration test: 0.5 g of the conditioner sample was dispersed in 50 mL of deionized water, sonicated (40 kHz, 5 min) and allowed to stand for 24 h; The upper suspension was taken and the average particle size (D50) was measured by laser particle size analyzer; Calculate the particle size change rate: Change rate .
[0082] Functional group stability test: Take the saturated adsorption conditioner sample (after 5 cycles of experiment 1), dry it at 60℃ and grind it through a 200-mesh sieve; FTIR spectrometer (KBr pellet method) was used to scan 400-4000 cm -1 scope; Calculate the characteristic peak of carboxyl group (1720cm -1 ) Intensity decay rate: decay rate .
[0083] Mechanical strength test: Take 10g of the conditioner particles (1-3mm) and place them in the mold of the pressure testing machine; Apply pressure to 10 MPa at a rate of 5 mm / min and maintain pressure for 1 min; Collect the broken particles (<0.5mm) and calculate the crushing rate: crushing rate = .
[0084] Parallel experimental design: Three parallel samples were set up for all tests, and the data were expressed as mean ± standard deviation.
[0085] Experimental data: Table 4: Experiment 4 Material Stability Comparison Test Data Data analysis description: Example 1: The nanocarbon-humic acid composite structure formed by ultrasound-assisted intercalation effectively inhibited particle agglomeration (change rate 5.3%), and the carboxyl functional groups remained stable through the hydrogen bond network (attenuation rate 8.2%). Comparative Example 1 (no ultrasonic intercalation): Humic acid exists in a physically mixed form, and the particles agglomerate rapidly due to van der Waals forces (change rate 24.7%), and the exposure of carboxyl groups causes the attenuation rate to increase to 31.5%; Comparative Example 7 (excessive humic acid): Excessive humic acid (25%) weakened the supporting effect of the nanocarbon skeleton, the breakage rate increased to 27.3%, and the entanglement of the carboxyl group molecular chain intensified the degradation.
[0086] Experimental summary: This experiment reveals the synergistic protection mechanism of the long-term stability of the material by ultrasonic-assisted intercalation and nanocarbon skeleton support effect in the nanocarbon-based sustained-release conditioner by comparing the differences in material stability of different preparation processes. In Example 1, humic acid molecules are embedded in the nanocarbon layer through ultrasonic cavitation, and their carboxyl groups form a cross-linked hydrogen bond network with the hydroxyl groups on the surface of the nanocarbon, which significantly enhances the binding force between the particles. This structural characteristic makes the particle size change rate of the material only 5.3% after 24 hours of dispersion in water, and the carboxyl functional group decay rate is controlled at 8.2% after 5 adsorption cycles. However, in Comparative Example 1, due to the omission of the ultrasonic intercalation step, humic acid is only attached to the nanocarbon surface in the form of physical adsorption, the hydrogen bond cross-linking density is insufficient, and the particles are rapidly agglomerated due to van der Waals forces during the static process. The particle size change rate is as high as 24.7%, and the carboxyl decay rate rises to 31.5% simultaneously, confirming the irreplaceable role of ultrasonic intercalation in interface stabilization.
[0087] The ratio of humic acid to nanocarbon matrix directly affects the mechanical strength and compressive properties of the material. In Example 1, when the humic acid accounted for 18.5%, its molecular chain formed a three-dimensional interpenetrating network with the nanocarbon skeleton through π-π conjugation, which could not only buffer the external pressure but also maintain the rigid support structure of the nanocarbon. The crushing rate under 10MPa pressure was only 12.7%. In Comparative Example 7, the proportion of humic acid was increased to 25%, and the excessive molecular chain caused the nanocarbon pores to be blocked, the continuity of the skeleton structure was destroyed, the crushing rate increased to 27.3%, and the carboxyl peak attenuation rate increased to 22.4% due to the aggravation of molecular chain entanglement. This shows that precise control of the humic acid ratio is the key to balancing the flexibility and rigidity of the material.
[0088] The hierarchical pore structure of the nanocarbon matrix further provides a protective barrier for the stability of functional groups. In Example 1, the mesoporous-macroporous composite channels (2-50nm) reduce the direct contact between the humic acid carboxyl groups and water molecules through the spatial confinement effect. At the same time, the hydrophobic region on the nanocarbon surface (C=O groups account for >30%) inhibits the penetration of water molecules, significantly reducing the oxidative degradation rate of the carboxyl groups. In Comparative Example 1, because the interlayer intercalation structure was not constructed, the humic acid molecules were directly exposed to the aqueous environment. The carboxyl groups were rapidly lost due to hydrolysis reactions during multiple cycles, resulting in severe deterioration of the functional group stability. This further verifies the core contribution of the layered composite design and pore synergistic protection to the long-term service performance of the material.
[0089] Test Example 5: Field Restoration Effect Comparative Test Experiment Description Purpose of the experiment: The soil improvement effects and crop growth response differences of the nano-carbon-based slow-release conditioner (Example 1) and its comparative examples (Comparative Examples 5 and 6) in actual saline-alkali environments were verified.
[0090] Experimental steps: Field test area setting: Moderately salinized farmland was selected (initial pH = 8.9, EC = 12.3 dS / m, SAR = 18.4); The experimental plot was divided into 3m×3m, and 3 replicates were set for each treatment group; Till the soil to a depth of 20 cm and remove weeds and stones.
[0091] Conditioner application and sowing: The conditioner (Example 1, Comparative Example 5 / 6) was evenly spread on the soil surface at a dosage of 2.5 kg / m²; Rotary tillage and mix well (depth 15 cm), and water to 70% of field water capacity; Corn (variety: Zhengdan 958) was sown with a row spacing of 50 cm and a plant spacing of 25 cm.
[0092] Soil sample collection and testing: pH measurement: 0d, 15d, and 30d after application, take mixed samples from the 0-20cm soil layer, and let the suspension of soil:water = 1:2.5 stand for 30min, and measure the pH with a pH meter; SAR calculation: 30-day-old soil samples were taken, 1:5 extract (deionized water) was shaken for 1 hour, and the Na + , Ca 2 + Mg 2+ Concentration, calculate SAR value: ; Statistics of seedling emergence rate: Count the number of seedlings emerging in each plot 14 days after sowing and calculate the ratio.
[0093] Environmental condition control: During the experimental period, the average daily temperature was 22-28°C, and supplementary irrigation was used to maintain soil moisture > 60% under natural rainfall conditions; The application of any other fertilizers or pesticides is prohibited.
[0094] Experimental data: Table 5: Comparative test data of field restoration effect in Experiment 5 Data analysis description: Example 1: pH-responsive cross-linker coating and gradient ion exchange synergistically reduced pH by 1.6 after 30 days, SAR decreased by 54.2%, and corn emergence rate reached 86.7%; Comparative Example 5 (no cross-linking agent coating): Rapid nutrient loss resulted in a pH decrease of only 0.7, insufficient SAR improvement (-28.9%), and a seedling emergence rate of 63.4%; Comparative Example 6 (Ca 2+ Excessive Ca 2+ It caused soil compaction, SAR dropped by 12.7%, corn root development was hindered, and the emergence rate was only 58.1%.
[0095] Experimental summary: This experiment verified the multi-stage synergistic repair mechanism of the nano-carbon-based slow-release conditioner through practical field application. In Example 1, the pH-responsive cross-linking agent coating layer was gradually degraded under the action of saline-alkali soil microorganisms, and the released humic acid carboxyl groups worked together with the hydroxyl groups on the surface of the nano-carbon to continuously neutralize the soil alkaline substances (such as Na2CO3). The pH dropped by 1.6 within 30 days, which was significantly better than 0.7 in Comparative Example 5. This process is closely related to the slow-release acid reservoir formed by the humic acid intercalation, and its carboxyl groups converted OH into OH through ion exchange. - Fixed as water molecules, while releasing H +The alkalinity is neutralized, and the precise control of the cross-linker molecular weight (60kDa) ensures that the acid release rate matches the salt tolerance threshold of the crop, avoiding local over-acidity that damages the root system, and ultimately achieving a corn emergence rate of 86.7%.
[0096] The gradient ion replacement mechanism plays a key role in soil structure improvement. 2+ Rapid replacement of Na + (SAR decreased by 54.2%) while reducing the sodium adsorption ratio, the internal PO4 3- With excess Ca 2+ CaHPO4 cement is generated to reshape the soil aggregate structure and increase the porosity (>35%), providing a breathable environment for the corn root system. 2+ At an excessive loading level (1.0 mol / L), excessive cement blocks soil pores, leading to compaction. SAR decreased by only 12.7%, while increased root penetration resistance reduced the emergence rate to 58.1%. This suggests that optimizing the calcium / phosphorus gradient loading ratio (1.5:1) is crucial for balancing desalination and structural improvement.
[0097] The multi-level pore network of the nanocarbon matrix and the synergistic effect of humic acid further ensure the dynamic balance of nutrients and water. In Example 1, the mesopores (2-50nm) act as water transmission channels to maintain soil moisture stability, while the macropores (>50nm) provide storage space for the slow release of humic acid. Combined with the water retention properties of humic acid (contact angle <30°), the soil moisture is still maintained at >60% under natural rainfall fluctuations, creating a continuously suitable environment for seed germination. In Comparative Example 5, due to the lack of cross-linking agent coating, the nanocarbon pores are blocked by the rapidly released humic acid, the water transmission capacity is reduced, and the local alternation of dryness and wetness exacerbates the surface accumulation of salt, resulting in a seedling emergence rate of only 63.4%. This proves that the spatiotemporal matching of pore structure design and slow-release components is the core innovation to break through the bottleneck of traditional materials "desalination without seedling protection".
[0098] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. Nanocarbon-based slow-release saline-alkali land conditioner, characterized in that: It is composed of the following components in percentage by mass: Layered nanocarbon matrix: 45-65%, specific surface area 750-950m 2 / g, pore size is 2-50nm; Humic acid intercalation complex: 15-22%, carboxyl density 3.0-3.4mmol / g; pH-responsive crosslinker: 5-12%, dimethylaminoethyl methacrylate-acrylic acid copolymer, molecular weight 40-80 kDa; Calcium ion modifier: 5-15%, loaded in the form of CaCl2, with a loading concentration of 0.5-0.7 mol / L; Phosphate modifier: 5-10%, loaded in the form of NaH2PO4, with a loading concentration of 0.3-0.5 mol / L.
2. The nanocarbon-based slow-release saline-alkali land conditioner according to claim 1, characterized in that: The preparation method of the layered nanocarbon matrix comprises: The biomass raw material is heated to 550-650°C at 8-12°C / min under nitrogen protection and cracked for 1.5-2.5 hours, then mixed with KOH at a mass ratio of 1:2-1:4, and calcined at 800-900°C for 0.8-1.2 hours.
3. The nanocarbon-based slow-release saline-alkali land conditioner according to claim 1, characterized in that: The preparation method of the humic acid intercalation composite comprises: Humic acid and nano-carbon matrix are mixed in a mass ratio of 1:4.5-1:5.5, and ultrasonically treated at 35-45 kHz for 1.5-2.5 hours in a buffer solution with a pH of 8.5-9.
5.
4. The nano-carbon-based slow-release saline-alkali land conditioner according to claim 1, characterized in that: The loading method of the calcium ion modifier and the phosphate modifier includes: Alternately immerse in 0.5-0.7 mol / LCaCl2 solution and 0.3-0.5 mol / LNaH2PO4 solution, the cycle number is 3-5 times, and the immersion time each time is 1.0-1.5 hours.
5. The nano-carbon-based slow-release saline-alkali land conditioner according to claim 1, characterized in that: The coating method of the pH-responsive cross-linking agent includes: Fluidized bed spray technology is used, the spray rate is 3-5mL / min, the inlet air temperature is 50-60℃, and the coating amount is 8-12% of the total mass of the particles.
6. A gradient controlled release method for a nanocarbon-based slow-release saline-alkali land conditioner, characterized in that: The use of the nano-carbon-based slow-release saline-alkali land conditioner according to any one of claims 1 to 5 comprises the following steps: S1. pH-responsive salt adsorption: When the soil pH is greater than 8.3, the negative charge on the surface of the nanocarbon is enhanced, and the Na + , and its adsorption process conforms to the pseudo-second-order kinetic model; S2, microbial-driven nutrient release: soil microorganisms decompose crosslinkers to release available nitrogen and phosphorus, where the microbial activity threshold is a soil respiration rate ≥ 15 μgCO2 / g·h; S3, ion exchange dynamic equilibrium: each adsorption of 1 mol Na + Synchronously release 0.28-0.32 molCa 2+ .
7. The gradient controlled release method of the nano-carbon-based slow-release saline-alkali land conditioner according to claim 6, characterized in that: In the step S1: Na + The adsorption capacity is 4.2-5.0mmol / g; The equilibrium time in the pseudo-second-order kinetic model is 2.5-3.5h.
8. The gradient controlled release method of the nano-carbon-based slow-release saline-alkali land conditioner according to claim 6, characterized in that: In step S2, the release rate of available nitrogen is 0.5-0.8 mg / kg·d, and the release rate of available phosphorus is 0.3-0.6 mg / kg·d.
9. The gradient controlled release method of the nano-carbon-based slow-release saline-alkali land conditioner according to claim 6, characterized in that: In the step S3: The equilibrium constant log K of the ion exchange reaction is 2.8-3.1; Ca in soil solution after replacement 2+ The concentration is maintained at 0.8-1.2mmol / L.
10. An application of the method according to any one of claims 6 to 9 in saline-alkali land restoration, characterized in that: The application method is as follows: When the soil pH is greater than 8.3, apply 0.3-0.7 tons / mu of conditioner; When the available phosphorus content is less than 15 mg / kg, apply phosphate solution.
Citation Information
Cited By
Synergistic organic-inorganic complex microbial inoculant for promoting yield increase of rice and preparation method of synergistic organic-inorganic complex microbial inoculant
CN121195976A
A synergistic organic-inorganic compound microbial agent for promoting rice yield increase and a preparation method thereof
CN121195976B